Outcomes in patients with cardiac amyloidosis undergoing catheter ablation for atrial arrhythmias - Adrian M. Petzl, MD; Justice Oranefo, MD; Alireza Oraii, MD; Michael Riley, MD, PhD; David Lin, MD, FHRS; Ramanan Kumareswaran, MD; Robert D. Schaller, DO, FHRS; Gregory E. Supple, MD, FHRS; Timothy M. Markman, MD, FHRS; Gustavo Guandalini, MD; Matthew C. Hyman, MD, PhD; David S. Frankel, MD, FHRS; et al. (Heart Rhythm O2)
Background: Cardiac amyloidosis (CA) is characterized by atrial myopathy, which predisposes patients to atrial fibrillation (AF) and other atrial arrhythmias (AA). Although catheter ablation of AA is effective in the general population, its efficacy and safety in patients with CA remain unclear. Objective: The study aimed to evaluate outcomes in patients with CA undergoing catheter ablation for typical atrial flutter (TAFL) and left atrial (LA) arrhythmias and to assess the presence and influence of LA low-voltage areas (LVA) in the latter. Methods: We retrospectively analyzed patients with CA undergoing first-time ablation for TAFL or LA arrhythmias (AF, atypical atrial flutter, and focal tachycardia). For the latter group, LA electroanatomical mapping (EAM) quantified LVA burden and distribution. The primary outcome was arrhythmia recurrence at 1 year. Additionally, long-term outcomes over the maximum follow-up period were assessed and correlated with LVA. Results: The cohort included 36 patients (TAFL in 11, LA arrhythmias in 25; mean age 74 ± 7 years, 81% men, 64% wild-type transthyretin amyloidosis). Recurrence of any AA after 1 year occurred in 10 patients (40%) after LA arrhythmia ablation and in 3 patients (28%) after TAFL ablation (all new AA). LVA was seen in 73% of patients undergoing LA arrhythmia, and it occupied 50.4% of the LA surface, most commonly the posterior wall (53%). However, its presence did not correlate with long-term arrhythmia-free survival (P = 0.957). Procedure-related complications, particularly heart failure decompensation (16%), were important. Conclusion: Catheter ablation provides reasonable 1-year arrhythmia control in patients with CA experiencing TAFL or LA arrhythmias. However, long-term AA recurrence rates remain high.